Development of Integrated Renewable Energy Harvesting System - JAMALI, AHMAD FADLUL WAFI; Mohd, Prof. Madya Dr. Sofian; Qamarul Ezani Kamarudin (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Malaysia has a lot of potential for solar, wind, and wave energy because of its tropical environment and long coastline, however the output of the current systems, when installed separately, is uneven because of weather fluctuations. This project suggests and constructs an integrated renewable energy harvester system designed for Malaysia’s coastal circumstances, driven by the demand for a more reliable and sustainable energy solution. With power management and storage to guarantee continuous output, the system includes thin-film solar panels, a Savonius wind turbine, and a point absorber wave mechanism. The prototype was tested in real-world settings using locally sourced materials, and under ideal circumstances, it produced a peak output of roughly 14.6 V and 1.07 W. The findings support the viability, economics, and environmental compatibility of such a hybrid system for reliable renewable energy production in coastal areas.